Relationship between body composition and physical fitness of primary school learners from a predominantly rural province in South Africa - Howard Gomwe; Eunice Seekoe; Philemon Lyoka; Chioneso Marange; Denford Mafa (AOSIS, 2022)
Background: There is a lack of literature regarding the relationship that exists between body composition and physical fitness amongst primary school learners in South Africa. For the sake of public health purposes, it is important to investigate how body composition relates to physical fitness amongst primary school learners in the Eastern Cape province of South Africa. Aim: The aim of this study was to examine the relationship between body composition and physical fitness amongst South African primary school children. Setting: The study was conducted on a cohort of primary school learners in the Eastern Cape province, which is a predominantly rural province in South Africa. Methods: A school-based cross-sectional survey was conducted amongst 870 primary schoolchildren aged 9-14 years. Body composition and physical fitness measurements were measured and recorded using standardised measurement scales. Results: Of the 870 participants, 40.34% (n = 351) were boys and 59.66% (n = 519) were girls. The mean age of the participants was 11.04 ± 1.50 years. Boys had a significantly (p = 0.002) higher mean age (11.24 ±1.51 years) as compared to girls (10.91 ± 1.48 years). The results of the non-parametric Spearman's rho correlation coefficients revealed several significant and negative relationships between physical fitness and body composition measurements, which were stronger in girls than in boys. Conclusion: The findings call for public health authorities and other relevant policymakers to initiate the development and implementation of policies and interventions targeted at encouraging physical activity participation and healthy lifestyle amongst primary school learners in South Africa, especially amongst girls. Contribution: The study findings supports a relatively rich literature which suggests that girls are more flexible than boys and that negative relationships between body composition measurements and physical fitness characteristics exists, which are stronger in girls than in boys.